Preservation of Tolerance Values of The Dayak Tribe Hulu Ketapang District, West Kalimantan - Rianawati, Rianwati; Fuadi, Abdulloh; Dulhadi, Dulhadi; Muttaqin, Imron; Khairawati, Khairawati; Yapandi, Yapandi (Arfannur, 2024)
The diversity of ethnicities, cultures, and religions in Indonesian society is an undeniable fact. This diversity, of course, results in differences. These differences, if not properly managed, can lead to conflict. When the essence of tolerance like respecting other people’s differences as we embrace our own is upheld, this source of conflict and division in society can be prevented. The aim of this study is to identify and explain the tolerance values of the Dayak people, the social relations in their society, and the factors that prevent the preservation of religious tolerance based on the experience of the Dayak people of Lubuk Kakap Village. This research employed a qualitative research design with a phenomenological research method. Interviews and documentation were data collection procedures while data reduction, data display, and data verification are used as data analysis activities. The credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability of the data in this research were used as data validity testing. Based on the findings of the study, the tolerance values documented the life of the Dayak community of Lubuk Kakap Village are respect, appreciation of religion, belief and culture in social relations. The Dayak people interact in meetings and communal work which is called gotong royong. The Dayak people believe that the factors that prevent religious tolerance include small or big conflicts and individual disputes.